Tathbiq Namudzaj al-Ta’limi al-Iktisyafi fi Ta’lim al-Lughah al-‘Arabiyah Kamuhawalah Liinjazi Ta’allum Bima’had al-Mansyuriyyah Littarbiyah al-Islamiyyah Sepatan Tangerang - Rahma; Sahlani (INTIFA: Journal of Education and Language, 2024)
This research aims to reveal the application of the discovery learning model in learning Arabic at the Al-Mansyuriyah Sepatan Islamic boarding school, Tangerang. The method used in this study is the Classroom Action Research Method (PTK). This method is carried out in four stages, namely planning, action, observation and reflection. The four stages are carried out in one cycle which is carried out repeatedly with the same steps and remains focused on solving problems by self-discovery, self-investigation and information search using the Discovery Learning model. Based on the results of the research, it shows that student achievement using the Discovery Learning model has increased. This increase can be seen from the learning outcomes of each cycle that is carried out. In cycle 1, the average pretest score was 68.83 and the posttest average score was 75.5. In cycle 2, the average pretest score was 62.67 and the posttest average score was 89.00. The increase in learning outcomes can be seen from the average N-Gain value for each cycle, namely the average N-Gain cycle 1 is 0.22 and the average N-Gain cycle 2 is 0.70. From these results it proves that the Discovery Learning learning model applied by researchers can improve student achievement. مستخلص البحث يهدف هذا البحث لكشف تطبيق نموذج التعلم الاكتشافي في تعلم اللغة العربية بمعهد المنشورية سيفاتن تانجرانج. الطريقة المستخدمة في هذا البحث هي الطريقة البحث الإجرائي. تنفيذ هذه الطريقة في أربع مراحل، وهي التخطيط والإجراء والملاحظة والتفكير. تنفيذ المراحل الأربع في دورة واحدة وتنفيذها بشكل متكرر بنفس الخطوات وتظل تركز على حل المشكلات عن طريق الاكتشافى الذاتي والتحقيق الذاتي والبحث عن المعلومات باستخدام نموذج التعلم الاكتشافى. بناءً على نتائج البحث، فقد تبين أن إنجاز تعلم الطلاب باستخدام نموذج التعلم الاكتشافى قد زاد. يمكن رؤية هذه الزيادة من نتائج التعلم لكل دورة التي يتم تنفيذها. في الدورة الأولى، كان متوسط ​​قيمة الاختبار القبلي 68.83 و متوسط قيمة الاختبار البعدي 75,5. و في الدورة الثانية كان متوسط قيمة الاختبار القبلي 62,67  و متوسط قيمة الاختبار البعدي 89,00. يمكن رؤية نتائج التعلم من متوسط ​​قيمة N-Gain لكل دورة، وهو متوسط قيمة الكسب الطبيعى للدورة الأولى 0,22 و متوسط قيمة الكسب الطبيعى للدورة الثانية 0,70. من هذه النتائج يثبت أن نموذج التعلم الاكتشافي المطبق مع الباحثة يمكن أن يحسن إنجاز تعلم الطلاب.